2018
DOI: 10.3389/fpsyg.2018.02028
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Volume in Resistance Training on Inhibitory Control in Young Adults: A Randomized and Crossover Investigation

Abstract: Purpose: The aim of the study is to compare the effect of resistance training volume on inhibitory control in young adults with previous experience in resistance training.Method: All the 27 participants underwent 40-week experiment, divided in three training phases of 8-week duration. A washout period of 8 weeks between each of the training phases was carried out. The participants performed 1, 3, or 5 sets of the same exercises with equalized intensity (loading zones) and rest. Inhibitory control was assessed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…However, they did not have a fixed number of sets and duration of interset rest intervals among the three protocols. The differences in these variables among the resistance exercise protocols may influence the degree of postexercise IC improvements (Fortes et al, 2018), possibly by affecting some systems, including neuromuscular (Jenkins et al, 2015), metabolic (Kraemer et al, 1990), and perceptual systems (Woods, Bridge, Nelson, Risse, & Pincivero, 2004), for increasing neural activity in the brain. In the present study, we examined with the same number of sets and the same duration of interset rest intervals between HV-LRE and HRE.…”
Section: Discussionmentioning
confidence: 99%
“…However, they did not have a fixed number of sets and duration of interset rest intervals among the three protocols. The differences in these variables among the resistance exercise protocols may influence the degree of postexercise IC improvements (Fortes et al, 2018), possibly by affecting some systems, including neuromuscular (Jenkins et al, 2015), metabolic (Kraemer et al, 1990), and perceptual systems (Woods, Bridge, Nelson, Risse, & Pincivero, 2004), for increasing neural activity in the brain. In the present study, we examined with the same number of sets and the same duration of interset rest intervals between HV-LRE and HRE.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to number of sets, on the behavioral level, it was reported that younger adults performing three or five sets of a resistance exercise showed after a 8-week intervention period greater improvements in inhibitory control (i.e., assessed by accuracy and mean response time in the Stroop test) than younger adults performing one set of the same resistance exercise [363]. Because the abovementioned study did not apply neuroimaging techniques or quantify neurotrophic markers (e.g., BDNF) [363], future investigations are needed to elucidate the underlying neurobiological mechanisms.…”
Section: Influence Of Exercise Variables and Training Variables On Nementioning
confidence: 99%
“…Many studies have shown that aerobic exercise improves inhibitory control using the Stroop task in humans (Fortes et al, 2018 ; Tsuk et al, 2019 ). The current study shows that HIFT is also a valid training program that exerts a positive effect on inhibitory control.…”
Section: Discussionmentioning
confidence: 99%
“…This is an indication that HIFT is a valid and more effective training paradigm compared with HIIT in improving muscle strength. Strength training was shown to improve various cognitive abilities, like working memory and executive function (Cassilhas et al, 2007 ; Gibala et al, 2012 ; Fortes et al, 2018 ; Herold et al, 2019 ; Landrigan et al, 2019 ). It was also shown to increase the levels of brain-derived neurotrophic factor (BDNF), an important factor for neuronal plasticity and survival (Quiles et al, 2019 ; Mckay et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation